Lecturers’ Perspectives on The Use of Chat GPT (Generative Pre-training Transformer) in English Writing Classes - Rahmawati, Liza; Hanifa, Rizaldy (Universitas Negeri Padang, 2024)
This study aimed to figure out how English Language and Literature Department lecturers’ perspectives on the use of chat GPT (Generative Pre-training Transformer) in English writing classes. This research used a qualitative descriptive design. The participants in the study were eight English Language and Literature Department lecturers who have taught and currently teaching in writing classes and have found student assignments that use AI or chat GPT. The data were collected using open-ended questionnaires and interviews. The findings showed that English Language and Literature Department lecturers’ have a positive perspective on the use of chat GPT in writing class. Besides that, the data revealed some students still often misused the chat GPT to complete writing tasks. Related to this, lecturers apply strategies to detect student assignments that use AI assistance or Chat GPT by using Turnitin application and checking the students writing pattern. Therefore, educators or lecturers are strongly advised to be able to develop their potential in following the era of technological development by utilizing various applications that can detect student assignments using AI assistance or chat GPT and the like.